Genotyping natural hybrids of Cryptocoryne purpurea in Borneo and Peninsular Malaysia - Roslan, Hairul Azman; Isa, Ipor; Cheksum, Tawan; Jacobsen, N.; Wongso, Suwidji; Idei, Takashige; Nurul Hafizah, Muhd Ariff (Universiti Malaysia Sabah, 2010)
A preliminary study was undertaken on the genotype of Cryptocoryne purpurea and the application of fingerprinting to study the genetic relatedness of population from four different localities, namely Kota Tinggi (Johor), Tasik Bera (Pahang), Lundu (Sarawak) and Sungai Lawak (Kalimantan). A total of 20 reproducible bands were generated and unique bands were found in all localities that demonstrated some degree of variations among the samples. Dendrograms and genetic similarity indices generated using NYSYSpc ver. 2.2 clearly divided C. purpurea hybrids into two clusters based on geographical distribution.